2-Acetamido-N-benzyl-1,4-imino-1,2,4-trideoxy-L-ribitol - Harding, C; Watkin, D; Rountree, J; Butters, T; Wormald, M; Dwek, R; Fleet, G (2005)
The molecular structure of 2-Acetamido-N-benzyl-1,4-imino-1,2,4-trideoxy-L-ribitol was investigated. The relative configuration of the stereocentres in a potential hexosaminidase inhibitor, the compound, prepared from D-lyxonolactone, had been established using X-ray crystallographic techniques. The compound was crystallized by cooling a warm solution in acetonitrile, forming clear block-like crystals. All the hydrogen (H) atoms of the compound were observed in a difference electron-density map.